Breastfeeding of children with special health needs: An integrative review (Research, Society and Development, 2021)
This review aim to know the scientific production about the difficulties and facilities of breastfeeding children with special health needs. This is an integrative review conducted in the PubMed, Lilacs, BDENF and INDEX Psychology databases by combining the following descriptors: breast feeding OR breastfeeding OR infant AND disabled children OR cerebral palsy OR down syndrome without language restriction and period. The research was guided by the following question: "What has been produced about the difficulties and facilities found in the breastfeeding process of children with special health needs?". Eleven articles were selected, four use a qualitative approach, five were quantitative and two were quanti-qualitative. Among the factors that can influence the breastfeeding of children with special health needs, difficulties were highlighted, such as lack of support, discouragement, hospitalization and negative feelings and among the facilities, previous experiences with breastfeeding and support from health professionals were reported. The importance of the role of the family and health services in assisting in the establishment of breastfeeding and its maintenance is emphasized.